Cutting off Cardiologists: The Disappeared in “Puro corazón” by Luisa Valenzuela - Diane E. Marting (Studies in 20th & 21st Century Literature, 2015)
Luisa Valenzuela’s neglected short story “Puro corazón” ('All Heart') uses surreal imagery and plot to write about the increasing violence in Buenos Aires during the time immediately prior to the Dirty War (la Guerra Sucia). By mimicking a police report, Valenzuela’s story manages to reproduce the experience of censorship and repression that denied the fate of the disappeared. This article shows how the story forges ludic connections between the human body (especially hearts, blood, and cardiologists), the censorship and repression in the early 1970s in Argentina, and the discourse that marked the official response to los desaparecidos, the disappeared.
Keywords: Luisa Valenzuela; " Puro corazón”; surrealism; Argentina; Dirty War; Guerra Sucia; Strange Things Happen Here; Aquí pasan cosas raras; the Disappeared; desaparecidos